Vulnérabilité des aires protégées du Bénin à l’invasion de Ageratum conyzoides L. (Asteraceae) en rapport avec les changements climatiques - A. K. G. Djotan; A. K. N. Aoudji; G. C. R. Gbaguidi; G. S. Akouehou; J. C. Ganglo (European Scientific Journal, ESJ, 2018)
Fighting against invasive species is a great challenge that requires knowledge about their potential distribution areas. Ageratum conyzoides is an invasive species in several African countries including Benin. In order to analyze the vulnerability of protected areas of Benin to the invasion of this species, and to guide managers of these areas to fight against invasions, this study used MaxEnt to model the ecological niche of the species under the current and future climates, horizon 2055 RCP 4.5 and RCP 8.5 scenarios. Environmental data and presence data were gathered respectively from the data bases of AfriClim and GBIF. From the current to the future climates, the potentially suitable areas for the distribution of the species shift from the center to the south of Benin. So, about 75%, 51% and 65% of Benin’s total area are respectively suitable under present climate, and future’s ones (RCP4.5 and RCP8.5). Only about 16% and 43% of this area are absolutely unsuitable and absolutely suitable to the species. As for protected areas, about 29% and 25% of their total area are respectively not vulnerable, and vulnerable to Ageratum conyzoides. Present climate, and future’s ones (RCP4.5, and RCP8.5) held respectively about 62%, 28%, and 48% of protected areas total superficies vulnerable to Ageratum conyzoides.